On The Soul. - Goldblatt, Mark (Philosophy Now)
The article offers the author's insights on the nature of human soul. The author defines soul as the voice inside one's head, a neurological phenomenon that is merely a brain activity, and an immaterial essence. He says that he is not the thing he encounters but the thing doing the encountering. He explains consciousness which is the thing emerging from sense data comprised of memory and language and relates it to cotton candy.